Pengaruh kompetensi wirausaha, motivasi berwirausaha, dan lingkungan sosial terhadap minat berwirausaha - Wahidatul Qomariya; Eka Hendi Andriansyah (Jurnal Pendidikan Ekonomi (JUPE), 2025)
This study aims to explain the influence of entrepreneurial competence, entrepreneurial motivation, and social environment on interest in entrepreneurship. This research uses a sample of 139 XI IPS students with a quantitative method and Structural Equation Modeling (SEM) analysis, assisted by WarpPLS Version 7.0 software. The results show that entrepreneurial motivation has a significant effect on interest in entrepreneurship of 39.7%. Therefore, it is hoped that schools can pay attention to increasing entrepreneurial motivation in order to enhance students' interest in entrepreneurship. Support for entrepreneurial motivation can be done through several means, including providing contextual learning about entrepreneurship, developing entrepreneurship into extracurricular activities, and utilizing the school's social environment located in industrial areas for industrial visits.